House of suns - Reynolds, Alastair, 1966- (Orbit, 2020)
Six million years ago, at the dawn of the star-faring era, Abigail Gentian fractured herself into a thousand male and female clones, which she called shatterlings. She sent them out into the galaxy to observe and document the rise and fall of countless human empires. Since then, every two hundred thousand years, they gather to exchange news and memories of their travels. Only there is no gathering. Someone is eliminating the Gentian line. And now two star-crossed shatterlings must determine exactly who, or what, their enemy is, before they are wiped out of existence.